2018
DOI: 10.3389/fmicb.2018.02561
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Genomic Analyses of Pseudomonas aeruginosa Podovirus TC6: Establishment of Genus Pa11virus

Abstract: Phages have attracted a renewed interest as alternative to chemical antibiotics. Although the number of phages is 10-fold higher than that of bacteria, the number of genomically characterized phages is far less than that of bacteria. In this study, phage TC6, a novel lytic virus of Pseudomonas aeruginosa, was isolated and characterized. TC6 consists of an icosahedral head with a diameter of approximately 54 nm and a short tail with a length of about 17 nm, which are characteristics of the family Podoviridae. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 63 publications
0
12
1
Order By: Relevance
“…Based on a BLAST analysis against the NCBI standard nucleotide database, a total of 177 genes were predicted ( Table S1 ), and nine genes encoding tRNAs (tRNA-Val, tRNA-Gln, tRNA-Arg, tRNA-Glu, tRNA-Ile, tRNA-Pro, tRNA-Leu, tRNA-Cys, and tRNA-Gly) were detected. A BLASTp analysis revealed that 166 proteins had homologs in other phages or bacteria; however, most of these proteins were assigned as hypothetical proteins, and no homologs of phage integrases, excisionases, repressors, or transposases were predicted which suggested that phage PN09 is a lytic phage [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Based on a BLAST analysis against the NCBI standard nucleotide database, a total of 177 genes were predicted ( Table S1 ), and nine genes encoding tRNAs (tRNA-Val, tRNA-Gln, tRNA-Arg, tRNA-Glu, tRNA-Ile, tRNA-Pro, tRNA-Leu, tRNA-Cys, and tRNA-Gly) were detected. A BLASTp analysis revealed that 166 proteins had homologs in other phages or bacteria; however, most of these proteins were assigned as hypothetical proteins, and no homologs of phage integrases, excisionases, repressors, or transposases were predicted which suggested that phage PN09 is a lytic phage [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…The P. aeruginosa phages TC6, O4, and IME180 showed significant relatedness and are very phylogenetically close to PA11. Therefore, these were classified as a new genus of phages infecting P. aeruginosa named Pa11virus ( Tang et al, 2018 ). Similarly, classifying PPAT and PPAY as Pa11virus contributed to the diversity and classification of Podoviridae .…”
Section: Discussionmentioning
confidence: 99%
“…The effect of this self-produced toxic protein must be considered while using such phases for biological therapy ( Watts, 2017 ). Pseudomonas phages GP100 and TC6 also contain hemagglutinin proteins ( Tang et al, 2018 ). This study isolated and identified two new virulent phage strains, which increases our understanding of the biodiversity of phages that can be used as antibacterial agents.…”
Section: Discussionmentioning
confidence: 99%
“…The isolated vB_KpnP_Klyazma phage has a morphology and genome structure typical of the Zobellviridae family [ 37 , 38 , 39 ]. Prior to being distinguished as the Zobellviridae family, such phages were grouped into the T7-like supergroup due to the virion morphology and homology of structural proteins [ 40 ].…”
Section: Discussionmentioning
confidence: 99%